Simultaneous Wavelength- and Mode-Division (De)multiplexing for High-Capacity On-Chip Data Transmission Link - Liangshun Han; Song Liang; Junjie Xu; Lijun Qiao; Hongliang Zhu; Wei Wang (IEEE Photonics Journal)
We present designs of wavelength-division-multiplexing (WDM) and mode-division-multiplexing (MDM) optical links using mode de/multiplexers (DE/MUXs) based on multimode interference (MMI) couplers with a tilt joint as a phase shifter. The properties of WDM-MDM links with three wavelengths and two optical modes are numerically studied by using 3-D beam propagation method. In the first design, the wavelength combiner is also an MMI coupler type. The insertion loss of the design is around 6 dB because of the inherent loss of the MMI combiner. The size of the main passive optical parts (mode DE/MUXs and wavelength combiner) of the design is only $10.4\ × 114.2\ μ\text{m}^{2}$ , making the design promising for future compact and high-capacity optical interconnection applications. In another design, arrayed waveguide gratings are used for wavelength multiplexing, leading to a lower insertion loss of the optical connections. For both designs, the mode crosstalk between the two different modes for the same wavelength are below −22 dB.